Redefining the Sociological Paradigm: Emile Durkheim and the Scientific Study of Morality - Prus, Robert (Qualitative Sociology Review, 2019)
Whereas Emile Durkheim (1858-1917) has long been envisioned as a structuralist, quantitative, and positivist sociologist, some materials that Durkheim produced in the later stages of his career—namely, Moral Education (1961 [1902-1903]), The Evolution of Educational Thought (1977 [1904-1905]), The Elementary Forms of the Religious Life (1915 [1912]), and Pragmatism and Sociology (1983 [1913-1914]) attest to a very different conception of sociology—one with particular relevance to the study of human knowing, acting, and interchange. Although scarcely known in the social sciences, Emile Durkheim’s (1993 [1887]) “La Science Positive de la Morale en Allemagne” [“The Scientific Study of Morality in Germany”] is an exceptionally important statement for establishing the base of much of Durkheim’s subsequent social thought and for comprehending the field of sociology more generally. This includes the structuralist-pragmatist divide and the more distinctively humanist approach to the study of community life that Durkheim most visibly develops later (1961 [1902-1903]; 1977 [1904-1905]; 1915 [1912]; 1983 [1913-1914]) in his career.